DESIGN OF MILITARY GEOINFORMATION SYSTEMS. PROBLEMS AND THEIR SOLUTIONS - POMORTSEVA, Olena; KOBZAN, Sergiy; GAMAYUN, Inna (Bulletin of Taras Shevchenko National University of Kyiv, Geography, 2023)
The article deals with the actual task of designing military geoinformation systems. Such GIS can significantly simplify the solution of an operational and tactical task for the Armed Forces of Ukraine. The analysis of similar geoinformation systems used by the armed forces of other countries shows that in the modern conditions of conducting military operations, it is impossible to do without digital technologies and geoinformation systems. The practical experience of solving such problems, in which topographical and geodetic data are used, is difficult due to the large volume of data and the complexity of their processing. Most of the calculations performed while preparing for the execution of a combat task are solved with the help of military information systems at the stage of setting and clarifying a task. The purpose of the article is to solve topographic and geodetic problems with the helping of geoinformation systems in a shorter time. The use of specialized military assignment systems makes it possible to significantly reduce the time needed to assess the situation and develop action plans for troops. The authors conducted studies of various types of complex information-processing algorithms. To solve the task of designing a geoinformation system for military use, it was suggested to use the existing geoinformation system. Such a GIS must be improved for use in the Armed Forces. It is possible to perform the task by introducing a programming language for solving specific problems and cutting off unused modules. It is an important that throughout the entire life cycle it will be necessary to maintain the level of secrecy until the last stage of the project. Results. The authors developed an algorithm for designing a geoinformation system for military using.